TINJAUAN STATUS GIZI REMAJA. APAKAH ASPEK DEMOGRAFI BERPENGARUH? - Rini Lestari; Dorce Sisfiani Sarimin; Wastu Widya; Indah Indah (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Adolescence is one of the most important developmental stages in the human life cycle because it marks the transition from childhood to adulthood. During this phase, rapid changes occur in various aspects, including physical, biological, psychological, and social development. The purpose of this study was to determine the relationship between demographic factors and nutritional status among adolescents. A cross-sectional study design was used. The study was conducted at a public high school in Manado. The research was carried out in September 2025. The study population consisted of all 11th-grade students. The sample size was 60 participants. Stratified random sampling was used as the sampling technique. A research questionnaire was used as the research instrument. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between family income (p-value: 0.032) and no relationship between the number of family members (p-value: 0.059) and the nutritional status of adolescents. It is recommended that adolescents improve their knowledge of dietary patterns, especially for students who are either overweight or underweight.Keywords: Family Income, Adolescents, Nutritional Status.